Rosiglitazone Alleviates Mechanical Allodynia of Rats with Bone Cancer Pain through the Activation of PPAR-γ to Inhibit the NF-κB/NLRP3 Inflammatory Axis in Spinal Cord Neurons - Jie Fu; Baoxia Zhao; Chaobo Ni; Huadong Ni; Longsheng Xu; Qiuli He; Miao Xu; Chengfei Xu; Ge Luo; Jianjun Zhu; Jiachun Tao; Ming Yao (PPAR Research)
Bone cancer pain (BCP) is a serious clinical problem that affects the quality of life of cancer patients. However, the current treatment methods for this condition are still unsatisfactory. This study investigated whether intrathecal injection of rosiglitazone modulates the noxious behaviors associated with BCP, and the possible mechanisms related to this effect were explored. We found that rosiglitazone treatment relieved bone cancer-induced mechanical hyperalgesia in a dose-dependent manner, promoted the expression of peroxisome proliferator-activated receptor-γ (PPAR-γ) in spinal cord neurons, and inhibited the activation of the nuclear factor-kappa B (NF-κB)/nod-like receptor protein 3 (NLRP3) inflammatory axis induced by BCP. However, concurrent administration of the PPAR-γ antagonist GW9662 reversed these effects. The results show that rosiglitazone inhibits the NF-κB/NLRP3 inflammation axis by activating PPAR-γ in spinal neurons, thereby alleviating BCP. Therefore, the PPAR-γ/NF-κB/NLRP3 signaling pathway may be a potential target for the treatment of BCP in the future.